Direct electrochemical determination of environmentally harmful pharmaceutical ciprofloxacin in 3D printed flow-through cell - Dakošová, Olívia; Melníková, Eva; Naumowicz, Monika; Kolivoška, Viliam; Vaněčková, Eva; Navrátil, Tomáš; Labuda, Ján; Veteška, Peter; Gál, Miroslav (Chemosphere, 2023)
Rising amounts of antibiotic residues in wastewater cause serious problems including increased bacterial resistance. Wastewater treatment plants (WWTPs) do not, in the case of new, modern pharmaceuticals, ensure their complete removal. Ciprofloxacin (CIP) is one of many micropollutants that partially pass through WWTPs, implying that its monitoring is essential for the assessment of the water quality. In real sewage systems, the determination of CIP needs to be performed under flowing conditions, which calls for the deployment of inexpensive, robust, and easily integrable approaches such as electrochemical techniques. However, to the best of our knowledge, there is no report on the electrochemical determination of CIP in a flowing matrix. To bridge this gap, we perform here cyclic and square-wave voltammetric sensing study of CIP employing boron-doped diamond screen printed electrodes in a custom-made 3D printed flow-through cell to mimic conditions in real sewage systems. An irreversible two-step oxidation of CIP is demonstrated, with the first step providing clear Faradaic response as analytically relevant signal. This response was found to scale with the sample flow rate according to the prediction given by Levich equation. Our work provides an in-depth inspection of the electrochemical response of CIP under controlled-convection conditions, which is an essential prerequisite for monitoring this antibiotic in real flowing sewage systems.
Keywords: Pharmaceutical Preparations; Printing, Three-Dimensional; Diamond; diamant; Wastewater; léčivé přípravky; 3D printed flow-through cell; Boron-doped diamond electrode; elektrochemické techniky; 3D tisk; Electrochemical Techniques; odpadní vody; Anti-Bacterial Agents; Antibiotics; ciprofloxacin; Electrochemical sensing; Electrodes; Sewage; elektrody; antibakteriální látky; Ciprofloxacin